Factors Associated With Eye Complaints Among Welders at PT. X In Batam City - Yolanda Sari, Chinta; Siddiq Ilhamsyah, Muhammad; Anggun Ramadhani, Natasyah; Amanda Tobing, Silvia; Talos Pangaribuan, Roman; Khailla, Risda (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Occupational safety and health (OSH) is a critical aspect in the welding industry, which poses a high risk to workers' eye health. Exposure to ultraviolet radiation, hot metal splashes, and welding fumes can lead to eye disorders ranging from mild irritation to severe damage such as blindness. Objective: This study aimed to identify factors associated with eye complaints among welders at PT X in Batam City. Method: A quantitative approach with a cross-sectional study design was used. A total of 40 welders were selected as respondents through total sampling. Data were collected using questionnaires and interviews to measure variables such as safe behavior, OSH training, technical skills (OSH skills), and eye complaints. Data analysis was conducted using univariate and bivariate methods with the chi-square test at a significance level of α = 0.05. Result and Discussion: The results showed that 60% of respondents exhibited unsafe behavior, 62.5% had received OSH training, 70% possessed OSH skills, and 60% experienced eye complaints. A significant relationship was found between safe behavior, OSH training, and OSH skills with eye complaints (p=0.001). Conclusion: These findings highlight the importance of promoting safe work behavior, effective OSH training, and skill enhancement to prevent eye health problems among welding workers.